Attenuation measurements show that the presence of a TachoSil surgical patch will not compromise target irradiation in intra-operative electron radiation therapy or high-dose-rate brachytherapy. Issue 1 (December 2015) - Sarmento, Sandra; Costa, Filipa; Pereira, Alexandre; Lencart, Joana; Dias, Anabela; Cunha, Luís; Sousa, Olga; Silva, José; Santos, Lúcio
Abstract Background Surgery of locally advanced and/or recurrent rectal cancer can be complemented with intra-operative electron radiation therapy (IOERT) to deliver a single dose of radiation directly to the unresectable margins, while sparing nearby sensitive organs/structures. Haemorrhages may occur and can affect the dose distribution, leading to an incorrect target irradiation. The TachoSil (TS) surgical patch, when activated, creates a fibrin clot at the surgical site to achieve haemostasis. The aim of this work was to determine the effect of TS on the dose distribution, and ascertain whether it could be used in combination with IOERT. This characterization was extended to include high dose rate (HDR) intraoperative brachytherapy, which is sometimes used at other institutions instead of IOERT. Methods CT images of the TS patch were acquired for initial characterization. Dosimetric measurements were performed in a water tank phantom, using a conventional LINAC with a hard-docking system of cylindrical applicators. Percentage Depth Dose (PDD) curves were obtained, and measurements made at the depth of dose maximum for the three clinically used electron energies (6, 9 and 12MeV), first without any attenuator and then with the activated patch of TS completely covering the tip of the IOERT applicator. For HDR brachytherapy, a measurement setup was improvised using a solid water phantom and a Farmer ionization chamber. Results Our measurements show that the attenuation of a TachoSil patch is negligible, both for high energy electron beams (6 to 12MeV), and for a HDR192 Ir brachytherapy source. Our results cannot be extrapolated to lower beam energies such as 50 kVp X-rays, which are sometimes used for breast IORT. Conclusion The TachoSil surgical patch can be used in IORT procedures using 6MeV electron energies or higher, or HDR192 Ir brachytherapy.